(3ZGjI GdGfJaGY HGdHNT GdPi HWQa bhS GdEQJaGYs - (3CHh YHO GdQMef LeGd GdOjf YHO Gddg Hf Ndjd Hf jhSa GdeGQOjfjs
(3ChdgG (B:s
(3hHYO , aEfg SFd GdTjN LeGd GdOjf GdeGQOjfi Yf GdHNT HWQa bhS GdGQJaGY HGdQHY GdeLjH s
(3BNQgG (B:s
(3hGeG GdOGFQJjf (B( 1) (3GdXgQ hGdYUQ hGdMUJjf hGdSeJ aeYdhe JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B17(3C (B- (3U(B18(3Cs
(3ai GdeYgO fSNI CNQi HQbe (B100 (3adcs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B270s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B169 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs